Device profile of the XVision-spine (XVS) augmented-reality surgical navigation system: overview of its safety and efficacy. (2nd January 2021) - Dibble, Christopher F.; Molina, Camilo A.
ABSTRACT: Introduction : The field of augmented reality mediated spine surgery is growing rapidly and holds great promise for improving surgical capabilities and patient outcomes. Augmented reality can assist with complex or atypical cases involving challenging anatomy. As neuronavigation evolves, fundamental technical limitations remain in line-of-sight interruption and operator attention shift, which this novel augmented reality technology helps to address. Areas covered : XVision is a recently FDA-approved head mounted display for intraoperative neuronavigation, compatible with all current conventional pedicle screw technology. The device is a wireless, customizable headset with an integrated surgical tracking system and transparent retinal display. This review discusses the available literature on the safety and efficacy of XVision, as well as the current state of augmented reality technology in spine surgery. Expert opinion : Augmented-reality spine surgery is an emerging technology that may increase precision, efficiency, and safety as well as decrease radiation exposure of manual and robotic computer-navigated pedicle screw insertion techniques. The initial clinical experience with XVision has shown good outcomes and it has received positive operator feedback. Now that initial clinical safety and efficacy has been demonstrated, ongoing experience must be studied to empirically validate this technology and generate further innovation in this rapidly evolving field.